2006
DOI: 10.1007/s10825-006-8825-2
|View full text |Cite
|
Sign up to set email alerts
|

Channel noise modelling of nanoMOSFETs in a partially ballistic transport regime

Abstract: In this paper, we present a novel compact model for channel noise in FETs where the effects of far-fromequilibrium transport are considered in a fundamental way. The intermediate range between the drift-diffusion and the ballistic transport regimes is covered through an analytical treatment based on Büttiker virtual probes approach to inelastic scattering. The channel noise is interpreted as due to the contribution of thermal noise at the source end and of shot noise associated with local ballistic transport a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…36 The channel is segmented using Büttiker probes and noise sources are associated to its individual elements. In contrast to this work, thermal noise is associated with the source side of the channel, whereas shot noise is modeled at the drain side and attributed to the local ballistic transport at the last channel segment.…”
Section: Shot Noise Suppressionmentioning
confidence: 99%
“…36 The channel is segmented using Büttiker probes and noise sources are associated to its individual elements. In contrast to this work, thermal noise is associated with the source side of the channel, whereas shot noise is modeled at the drain side and attributed to the local ballistic transport at the last channel segment.…”
Section: Shot Noise Suppressionmentioning
confidence: 99%
“…Although it can be concluded from the experimental results and the simulation results that shot noise is suppressed in nano-MOSFET [3,4,6,11], and the Fano is closely related to the device structure parameters and working parameters, there are still no suppression mechanism and shot noise suppression strength in-depth theoretical study. The research showed that noise expression in nano-MOSFET, and considering the existence of Fermi and Coulomb at the same time, only the Fermi or Coulomb interaction, or neither with simple analysis [7,10]; The research established the total suppression factor formula of shot noise in ballistic MOSFET, with a simple explain and discussion on the relationship between the suppression factor and the gate voltage, but the formula for Coulomb and Fermi suppression was not analyzed respectively [6, 7, 10, 12 -14].…”
Section: Introductionmentioning
confidence: 86%
“…When the channel length is in the range of sub 100 nm, carrier transport mechanism shifts from drift diffusive to quasi-ballistic or even to ballistic transport (Quasi-ballistic transport means less carrier scattering times; ballistic transport is limiting case that the carrier shot noise [2 -9]. The research has demonstrated the role of the Fermi and Coulomb correlations in the nano-MOSFET, and the simulation has been carried out [6,7,10]. The Fermi correlation effects carrier injection in the contact side, and the higher carriers degenerate, the stronger the suppression of Fermi on the shot noise;the Coulomb correlation can change carriers, and the stronger the space charge effect, the stronger the suppression of Coulomb on the shot noise .…”
Section: Introductionmentioning
confidence: 99%
“…An emerging direction to model MOSFET channel noise is based on the non-equilibrium shot noise, and has been applied to RT devices including short-channel MOSFETs [22], ballistic or quasi-ballistic MOSFETs [24], [25], and silicon nanowire FETs [26]. The channel noise for MOSFETs in strong inversion and saturation can be expressed as [22] 2…”
Section: ) Gate Resistance (Rg)mentioning
confidence: 99%